Protecting Postextubation Respiratory Failure and Reintubation by High-Flow Nasal Cannula Compared to Low-Flow Oxygen System: Single Center Retrospective Study and Literature Review - Lee, Minhyeok (Acute Crit Care, 2019)
BACKGROUND: Use of a high-flow nasal cannula (HFNC) reduced postextubation respiratory failure (PERF) and reintubation rate compared to use of a low-flow oxygen system (LFOS) in low-risk patients. However, no obvious conclusion was reached for high-risk patients. Here, we sought to present the current status of HFNC use as adjunctive oxygen therapy in a clinical setting and to elucidate the nature of the protective effect following extubation. METHODS: The medical records of 855 patients who were admitted to the intensive care unit of single university hospital during a period of 5.5 years were analyzed retrospectively, with only 118 patients ultimately included in the present research. The baseline characteristics of these patients and the occurrence of PERF and reintubation along with physiologic changes were analyzed. RESULTS: Eighty-four patients underwent HFNC, and the remaining 34 patients underwent conventional LFOS after extubation. Physicians preferred HFNC to LFOS in the face of high-risk features including old age, neurologic disease, moderate to severe chronic obstructive pulmonary disease, a long duration of mechanical ventilation, low baseline arterial partial pressure of oxygen to fraction of inspired oxygen ratio, and a high baseline alveolar–arterial oxygen difference. The reintubation rate at 72 hours after extubation was not different (9.5% vs. 8.8%; P=1.000). Hypoxic respiratory failure was slightly higher in the nonreintubation group than in the reintubation group (31.9% vs. 6.7%; P=0.058). Regarding physiologic effects, heart rate was only stabilized after 24 hours of extubation in the HFNC group. CONCLUSIONS: No difference was found in the occurrence of PERF and reintubation between both groups. It is worth noting that similar PERF and reintubation ratios were shown in the HFNC group in those with certain exacerbating risk factors versus not. Caution is needed regarding delayed reintubation in the HFNC group.